POLIURETAN MINYAK AMPAS KOPI ARABIKA ( Coffea arabica L.) - Indra Masmur; Jumadi Septian Sihombing; Mimpin Ginting (JURNAL KIMIA MULAWARMAN, 2021)
Polymerization of coffee grounds oil with Diphenyl Methane 4,4 Diisocyanate (MDI), epoxidation with performic acid and H2SO4(p) catalyst at 40-45°C, followed by hydrolysis to obtain polyols. The synthesis was carried out by reacting the polyol with Diphenyl Methane 4,4 Diisocyanate (MDI) with a ratio (polyol: MDI) 9:1; 8:2 ; 7:3 ; 6:4 ; 5:5 (v/v) in dichloromethane solvent. Each was characterized and the density values were 0.9086 gr/cm to 0.4979 gr/cm-1, the tensile strength and elongation values were 0.113 Mpa to 0.299 Mpa and 3.23% to 6.85%, respectively.